Implementation of Organic Waste Processing Through Eco Enzyme Production Activities at Johar Baru Kindergarten, Central Jakarta - Ade Hariyani; Rita Aryani; Muna Sovia Mamba’usa’adah; Mona El liza; Murni Mei Asmorowati; Rosmidar Yati; Najjah Barokah (Universitas Panca Sakti Bekasi, 2024)
The aim of this Community Service Program (PKM) is to create an engaging and enjoyable learning experience on organic waste processing for participants through the production of eco enzyme conducted from October 20, 2023, to November 25, 2023. The eco enzyme production involves three stages: planning, implementation, and evaluation. Methods employed in the planning stage include observation, interviews, and Focus Group Discussion (FGD). The implementation phase follows the created Lesson Plan (RPP). The evaluation phase reflects on the planning and execution. Results indicate an increase in knowledge among students and educators at TK Johar Baru, Central Jakarta, regarding the production and benefits of eco-enzymes. Initially, the issue at TK Johar Baru was the underutilization of recycled materials and a lack of understanding about waste management. This PKM activity has enhanced the awareness of teachers and students at TK Johar Baru in processing organic waste through eco enzyme production.